2020
DOI: 10.1111/jcmm.14838
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes transmit T790M mutation‐induced resistance in EGFR‐mutant NSCLC by activating PI3K/AKT signalling pathway

Abstract: Emerging evidence has shown that exosomes derived from drug-resistant tumour cells are able to horizontally transmit drug-resistant phenotype to sensitive cells. However, whether exosomes shed by EGFR T790M-mutant-resistant NSCLC cells could transfer drug resistance to sensitive cells has not been investigated. We isolated exosomes from the conditioned medium (CM) of T790M-mutant NSCLC cell line H1975 and sensitive cell line PC9. The role and mechanism of exosomes in regulating gefitinib resistance was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…[ 10 ] Thus, inhibiting PI3K/Akt pathway can restore the sensitivity of NSCLC cells to TKIs and thereby reduce the resistance of NSCLC cells to TKIs therapy. [ 11 ] Indeed, recent studies reveal that the PI3K/Akt pathway inhibition along with EGFR suppression is beneficial to NSCLC treatment. [ 12 ] There results prompted us to search for an alternative formulation that can treat the TKI‐resistant NSCLC effectively.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Thus, inhibiting PI3K/Akt pathway can restore the sensitivity of NSCLC cells to TKIs and thereby reduce the resistance of NSCLC cells to TKIs therapy. [ 11 ] Indeed, recent studies reveal that the PI3K/Akt pathway inhibition along with EGFR suppression is beneficial to NSCLC treatment. [ 12 ] There results prompted us to search for an alternative formulation that can treat the TKI‐resistant NSCLC effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-derived exosomes can be detected in the blood and body uids of patients. It has been demonstrated that exosomes can affect the therapeutic response and induce drug resistance in tumor cells [27]. Recent research has suggested that drug-resistant cells transmit drug resistance information to drug-sensitive cells through extracellular vesicles [28].…”
Section: Discussionmentioning
confidence: 99%
“…This also shows that tumor-derived exosomes can be objects of liquid biopsy, re ecting the tumor burden and drug resistance. It has been proved that exosomes can affect the therapeutic response and induce drug resistance of tumor cells [29]. Recent research have suggested that drug-resistant cells transfer drug resistance to drug-sensitive cells through miRNAs and drug e ux mercury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Yan Zhang[34]et al con rmed that exosomes miR-214 from Ge tinib-resistant PC9-GR could inhibit apoptosis in vitro, in vivo inhibit tumor growth and consequently gain Ge tinib resistance in EGFR-mutant lung cancer. Liu[29] et al found that miR-522-3p in exosomes from H1975 cells can increase the resistance of Ge tinib to PC9 cells.…”
mentioning
confidence: 99%